2008
DOI: 10.1016/j.molbiopara.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Release of metabolic enzymes by Giardia in response to interaction with intestinal epithelial cells

Abstract: Giardia lamblia, an important cause of diarrheal disease, resides in the small intestinal lumen in close apposition to epithelial cells. Since the disease mechanisms underlying giardiasis are poorly understood, elucidating the specific interactions of the parasite with the host epithelium is likely to provide clues to understanding the pathogenesis. Here we tested the hypothesis that contact of Giardia lamblia with intestinal epithelial cells might lead to release of specific proteins. Using established co-cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
139
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(149 citation statements)
references
References 44 publications
9
139
0
1
Order By: Relevance
“…Transcriptional changes in G. intestinalis during interaction with intestinal epithelial cells were also monitored by microarray analysis of G. intestinalis cDNAs, and indicated up-regulation of genes encoding enolase, cysteine proteinase, arginine deiminase and oxygen defence proteins (Ringqvist et al, 2011). Interestingly, contact of G. intestinalis with epithelial cells resulted in the release of metabolic enzymes (arginine deaminase, ornithine carbamoyltransferase and enolase) from G. intestinalis, which disabled host immune factors including nitric oxide (Ringqvist et al, 2008). A previous study also demonstrated that the excretory-secretory products (ESP) of G. lamblia contained major antigen(s) responsible for protection against infection in mice ( Kaur et al, 1999Kaur et al, , 2001.…”
Section: Exosome and Microvesicles Content Can Alter Neighbouring Cellsmentioning
confidence: 99%
“…Transcriptional changes in G. intestinalis during interaction with intestinal epithelial cells were also monitored by microarray analysis of G. intestinalis cDNAs, and indicated up-regulation of genes encoding enolase, cysteine proteinase, arginine deiminase and oxygen defence proteins (Ringqvist et al, 2011). Interestingly, contact of G. intestinalis with epithelial cells resulted in the release of metabolic enzymes (arginine deaminase, ornithine carbamoyltransferase and enolase) from G. intestinalis, which disabled host immune factors including nitric oxide (Ringqvist et al, 2008). A previous study also demonstrated that the excretory-secretory products (ESP) of G. lamblia contained major antigen(s) responsible for protection against infection in mice ( Kaur et al, 1999Kaur et al, , 2001.…”
Section: Exosome and Microvesicles Content Can Alter Neighbouring Cellsmentioning
confidence: 99%
“…The proteins released by G. duodenalis upon exposure to host cells have been characterised in a study by Ringqvist et al (2008). These proteins are commonly referred to as the excretory/secretory proteins or ESP.…”
Section: Host-parasite Interactionsmentioning
confidence: 99%
“…In the study by Ringqvist and co-workers, trophozoites were incubated with CaCo-2 cells in serum free media and proteins extracted from the growth media and analysed using 2D-PAGE. Five protein spots were identified by mass spectrometry, 3 of which are G. duodenalis proteins, with the other two being human derived (Ringqvist, et al, 2008). The three G. duodenalis proteins, ornithine carbamoyl transferase (OCT), arginine deiminase (ADI) and enolase, are all metabolic enzymes.…”
Section: Host-parasite Interactionsmentioning
confidence: 99%
“…74 Results have shown host-cell stimulated secretion of giardial proteins, which have the potential to be involved in the immunological events during initiation of infection and subsequent survival of the parasite in the host. In vitro studies with recombinant arginine deiminase showed that the secreted Giardia proteins could disable host innate immune factors such as nitric oxide production.…”
Section: Nitric Oxide In Giardiasismentioning
confidence: 99%
“…These fl avodiiron proteins were fairly recently identifi ed in a restricted group of microaerobic protozoa, including G. intestinalis. Ringqvist et al 74 proposed that in G. intestinalis the primary function of fl avodiiron proteins is to effi ciently scavenge O 2 , allowing this microaerobic parasite to survive in the human small intestine, thus promoting its pathogenicity.…”
Section: Nitric Oxide In Giardiasismentioning
confidence: 99%